2021
DOI: 10.3389/fcimb.2021.628327
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Microbiome Variation in Early Childhood Caries of Children 3–6 Years of Age and Its Association With Iron Deficiency Anemia and Extrinsic Black Stain

Abstract: ECC is a common clinical manifestation of the oral cavity in childhood and Iron deficiency-anemia (IDA) is a high-risk factor but extrinsic black stain on the tooth surface is a protective factor for caries. There is limited information about oral microecological change in early children who suffer from ECC with IDA and extrinsic black stain (BS). This study enrolled 136 children aged 3-6 years. Dental caries and teeth BS were examined. Saliva was collected for 16S rRNA gene and fingertip blood were for Hemogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Phylum Proteobacteria, Firmicutes, Bacteroidetes, Fusobacteria, and Actinobacteria appeared to dominate in the two groups of children. [15][16][17][18]23,24 Phylum Firmicutes had a higher percentage of children with ECC but had less diversity than CF children. [15][16][17][18] Phylum Firmicutes is one of the most powerful taxonomies because it includes many bacteria with diverse characteristics (phylogenetic, phenotypic, chemotaxonomic, and pathogenic).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylum Proteobacteria, Firmicutes, Bacteroidetes, Fusobacteria, and Actinobacteria appeared to dominate in the two groups of children. [15][16][17][18]23,24 Phylum Firmicutes had a higher percentage of children with ECC but had less diversity than CF children. [15][16][17][18] Phylum Firmicutes is one of the most powerful taxonomies because it includes many bacteria with diverse characteristics (phylogenetic, phenotypic, chemotaxonomic, and pathogenic).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18]23,24 Phylum Firmicutes had a higher percentage of children with ECC but had less diversity than CF children. [15][16][17][18] Phylum Firmicutes is one of the most powerful taxonomies because it includes many bacteria with diverse characteristics (phylogenetic, phenotypic, chemotaxonomic, and pathogenic). 29 Phylum Firmicutes was dominated first by the Order Lactobacillales of the genus Streptococcus (Streptococcus mutans and Streptococcus sobrinus) and Lactobacillus salivarius (Lactobacillus salivarius, Lactobacillus fermentum, Lactobacillus gasseri, and Lactobacillus mucosae).…”
Section: Discussionmentioning
confidence: 99%
“…ANOSIM analyses of the plaque microbiota also indicated significant differences in β diversity in the three plaque groups. Han et al analyzed the salivary microbiome diversity and reported significant differences in the microbial diversity of the BTS and control groups (7). Chen et al performed 16S rRNA sequencing and reported no statistically significant differences in the diversity and Unweighted Unifrac PCoA in the supragingival plaque microbiome between children with (n = 10) and without (n = 10) BTS (31).…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that the stains contain iron and copper in trace amounts along with a substantial proportion of organic matter (41). The formation of a sulfur and metal ion complex was considered responsible for pigmentation corresponding to zones of high concentrations of sulfur and iron/copper (7). Whether the presence of iron or copper is associated with BTS in primary dentition is still unclear and requires further investigations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation